Religiosity, halal labeling, product quality, and repurchase intention of Wardah customer - Laradise, Rista; Thamrin (Universitas Negeri Padang, 2023)
This study was conducted with the aim of analyzing and knowing the effect of religiosity, halal labeling and product quality on repurchase intentions of Wardah cosmetic users in Padang city which is mediated by purchase intention. The type of research conducted is quantitative research. The population of this study were students in Padang city who used Wardah cosmetics with a sample size of 200 respondents. Structural equation modeling used is smartpls 4.0 software. The results of this study indicate that (1) religiosity has a positive and significant effect on Purchase Intention, (2) Halal Labeling has a positive and significant effect on Purchase Intention, (3) product quality has a positive and significant effect on purchase intention, (4) repurchase intentions has a positive and significant effect on purchase intention, (5) religiosity has a positive and significant effect on repurchase intention with purchase intention as a mediating variable, (6) Halal Labeling has a positive and significant effect on repurchase intention through purchase intention as a mediating variable, (7) product quality has a positive and significant effect on repurchase intention through purchase intention as a mediating variable.